Chronotype-specific associations of meal timing patterns with cardiometabolic health in women: a cross-sectional study - Azadeh Lesani; Neda Soveid; Cain C. T. Clark; Bahar Barkhidarian; Fatemeh Gholami; Mansooreh Sadat Mojani-Qomi (Nutrition & Metabolism)
Abstract Background Although prior studies have examined meal timing and health, few have considered the impact of individual chronotypes and diurnal preference. This study explored how meal distribution and chronotype—morning (M-type) versus evening (E-type)— are associated with cardiometabolic health. Methods A cross-sectional study was conducted among 574 women in Tehran, Iran. Dietary intake was assessed through three 24-hour recalls and chronotype was determined via the Morningness-Eveningness Questionnaire. Cardiometabolic markers—including blood pressure (BP), glucose, lipids, insulin, and high-sensitivity C-reactive protein (hs-CRP)—were measured. Results In E-type individuals, higher breakfast energy intake was linearly associated with lower systolic [β 95% CI, -0.03 (-0.05 to -0.01)] and diastolic BP [-0.01 (-0.04 to -0.003)]. Afternoon energy intake was associated with lower BMI [-0.02 (-0.04 to -0.001)] and hs-CRP [-0.001 (-0.002 to -0.0006)] in E-type women. Additionally, U-shaped associations were found between breakfast intake and systolic BP (turning point: 23% of total energy intake (TEI)), and between afternoon intake and BMI (13% TEI) and hs-CRP (12% TEI). In contrast, higher dinner energy intake was linearly associated with greater BMI in the intermediate [-0.01 (-0.02 to -0.002)] and E-type group [0.05 (0.003 to 0.09)], respectively. Eating window was associated with higher fasting blood glucose [0.001 (0.002 to 0.003)] in E-type vs. M-type individuals. Conclusion Aligning energy intake with wake-up time—rather than delaying meals—may benefit evening chronotypes prone to circadian misalignment. Moderate breakfast and afternoon intake, with lower dinner intake, was related to better cardiometabolic health. Accordingly, longitudinal studies are advocated.